ESA1 Is Involved in Embryo Sac Abortion in Interspecific Hybrid Progeny of Rice. Issue 1 (15th February 2019) - Hou, Jingjing; Cao, Caihong; Ruan, Yini; Deng, Yanyan; Liu, Yaxin; Zhang, Kun; Tan, Lubin; Zhu, Zuofeng; Cai, Hongwei; Liu, Fengxia; Sun, Hongying; Gu, Ping; et al.
Abstract : ESA1 is involved in embryo sac abortion in hybrid backcross progeny derived from common wild rice and cultivated rice. Abstract: The emergence of sterile individuals in the hybrid backcross progeny of wild and cultivated rice limits the use of wild rice alleles for improving cultivated rice, but the molecular mechanisms underlying this sterility remain unclear. Here, we identified the semisterile introgression line YIL42, derived from a cross between the indica rice variety Teqing ( Oryza sativa ) and Oryza rufipogon accession YJCWR (Yuanjiang common wild rice), which exhibits semisterility. Using positional cloning, we isolated EMBRYO SAC ABORTION 1 ( ESA1 ), which encodes a nuclear-membrane localized protein containing an armadillo repeat domain. A mutation in ESA1 at position 1819 ( T 1819 C ) converts a stop codon into an Arg (R) codon, causing delayed termination of protein translation. Analysis of transgenic lines indicated that the difference in ESA1 protein structure between O. rufipogon –derived ESA1 and Teqing-derived esa1 affects female gamete abortion during early mitosis. Fertility investigation and expression analysis indicated that the interaction between ESA1   T1819 and unknown gene(s) of Teqing affects spikelet fertility of the hybrid backcross progeny. The ESA1   T1819 allele is present in O. rufipogon but absent in O. sativa, suggesting that variation in ESA1 may be associated with interspecific hybrid incompatibility between wild and cultivated rice. Our findings provide insight into the molecular mechanism underlying female sterility, which is useful for improving the panicle seed setting rate of rice and for developing a strategy to overcome interspecific hybrid sterility between cultivated rice and wild rice.